An Overview of Glycosylation and its Impact on Cardiovascular Health and Disease - Loaeza-Reyes, Karen Julissa; Zenteno, Edgar; Moreno-Rodríguez, Adriana; Torres-Rosas, Rafael; Argueta-Figueroa, Liliana; Salinas-Marín, Roberta; Castillo-Real, Lizet Monserrat; Pina-Canseco, Socorro; Cervera, Yobana Pérez (Frontiers in Molecular Biosciences, 2021)
The cardiovascular system is a complex and well-organized system in which glycosylation plays a vital role. The heart and vascular wall cells are constituted by an array of specific receptors; most of them are N- glycosylated and mucin-type O-glycosylated. There are also intracellular signaling pathways regulated by different post-translational modifications, including O-GlcNAcylation, which promote adequate responses to extracellular stimuli and signaling transduction. Herein, we provide an overview of N-glycosylation and O-glycosylation, including O-GlcNAcylation, and their role at different levels such as reception of signal, signal transduction, and exogenous molecules or agonists, which stimulate the heart and vascular wall cells with effects in different conditions, like the physiological status, ischemia/reperfusion, exercise, or during low-grade inflammation in diabetes and aging. Furthermore, mutations of glycosyltransferases and receptors are associated with development of cardiovascular diseases. The knowledge on glycosylation and its effects could be considered biochemical markers and might be useful as a therapeutic tool to control cardiovascular diseases.